A method for preparing porous SiO2-SiC ceramics
Patent Information
- Application Number
- CN202610873096.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-06-17
AI Technical Summary
专利文献CN105883812A公开了一种碳化硅的微波烧结生产工艺,以石英砂与煤焦炭为原料,经微波加热合成纯度较高、粒度不同的碳化硅微粉;该工艺目标产物为碳化硅微粉,烧结后产物仍为松散粉末,无法直接获得块体陶瓷材料,仍需后续加工才能用于制备多孔陶瓷部件;更无法原位形成多孔结构,难以满足隔热、过滤等应用需求
[0019]本发明通过调节碳粉粒径和硅碳比例,可有效控制SiO2-SiC陶瓷的孔径大小、分布和孔隙率。本发明采用粗颗粒碳粉D50为100~300μm,使微波加热时碳颗粒局部迅速耦合发热,形成高温区域;碳表面与二氧化硅发生高温反应释放气体,同时二氧化硅熔融,形成三维连通的多孔结构;碳除了作为热点促使二氧化硅熔融,也会挥发留下孔洞;通过调节碳粉的粒径和硅/碳原料的比例,可有效调控最终陶瓷的孔径大小和孔隙率。碳粉粒径对能不能形成多孔陶瓷非常关键,碳粉粒度越大,形成的局部高温区越大,生成的气泡越大,导致孔径增大;碳比例越高,反应生成气体越多,孔隙率越高;保温时间影响晶相演化与孔结构稳定性;时间过长可能导致孔塌缩;覆盖石英砂厚度防止碳氧化,维持局部还原气氛,促进SiO2熔融流动。
Smart Images

Figure CN122404015B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic materials technology, specifically relating to a method for preparing porous SiO2-SiC ceramics. Background Technology
[0002] Porous ceramic materials, due to their high specific surface area, low thermal conductivity, good permeability, and chemical stability, have broad application prospects in high-temperature filtration, catalyst supports, thermal insulation, sound absorption and noise reduction, and biomedicine. Among them, silicon carbide ceramics, with their excellent high-temperature resistance, high thermal conductivity, low coefficient of thermal expansion, good oxidation resistance, and corrosion resistance, have become ideal materials for use in extreme environments. However, silicon carbide has extremely strong covalent bonds, a low self-diffusion coefficient, and poor sintering activity, making it difficult to sinter below 2000℃. Generally, a second phase is introduced for sintering assistance, and densification is promoted through liquid-phase sintering or reaction sintering. Common sintering systems include: silica-bonded silicon carbide, mullite-bonded silicon carbide, alumina-bonded silicon carbide, and calcium hexaaluminate-bonded silicon carbide. Among these, the silica-bonded silicon carbide system has attracted attention due to its wide availability of raw materials, low cost, and broad process adaptability.
[0003] There are many methods for preparing porous silicon carbide ceramics, including solid-state pore-forming agent methods, foaming methods, emulsion methods, and freeze-drying methods. Solid-state pore-forming agent methods involve adding organic or inorganic pore-forming agents, which form pores through combustion or volatilization after sintering. However, the pore size distribution is uneven, and residual pore-forming agents may affect performance. Foaming methods introduce air bubbles through foaming agents or mechanical stirring, but the pore structure is difficult to control precisely, resulting in lower strength. Emulsion methods utilize oil-water emulsion templates to form pores, but the process is complex and costly. Freeze-drying methods form ordered pore structures through directional growth using ice crystal templates, but require sophisticated equipment and have low production efficiency. All of these methods generally suffer from problems such as complex processes, high costs, poor controllability of pore structure, and long production cycles.
[0004] In recent years, microwave sintering technology has been explored for application in the synthesis of silicon carbide materials due to its advantages such as rapid heating, uniform heating, and low energy consumption. Patent document CN105883812A discloses a microwave sintering process for silicon carbide, using quartz sand and coal coke as raw materials to synthesize silicon carbide micropowder with high purity and varying particle sizes via microwave heating. The target product of this process is silicon carbide micropowder; however, the sintered product remains a loose powder, making it impossible to directly obtain bulk ceramic materials. Further processing is required to prepare porous ceramic components. Furthermore, it cannot form porous structures in situ, making it difficult to meet the application requirements for heat insulation, filtration, and other applications.
[0005] Therefore, developing a simple, low-cost, and tunable porous SiO2-SiC ceramic preparation method has significant application value. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention proposes a novel method for preparing porous SiO2-SiC ceramics. This method is simple, efficient, and energy-saving. It utilizes the localized high-temperature effect of coarse carbon particles in a microwave field to induce a reaction between carbon and silicon dioxide, releasing gases. The reaction spontaneously generates pores, and the melting of silicon dioxide forms a binder phase, resulting in the spontaneous formation of a three-dimensionally interconnected porous bulk ceramic. This method not only overcomes the limitation of traditional microwave sintering, which only yields powder products, but also eliminates the need for external pore-forming agents, achieving in-situ control of the pore structure and enabling the direct preparation of porous SiO2-SiC ceramic bulks with controllable pore structures.
[0007] To achieve the above objectives, the technical solution adopted in this invention is: a method for preparing porous SiO2-SiC ceramics, comprising the following steps:
[0008] Step 1: Raw material mixing: Mix quartz sand and carbon powder at a silicon-to-carbon molar ratio of 1:1 to 1:3. The carbon powder particle size D50 is 100 to 300 μm.
[0009] Step 2, Compression Molding: The mixed raw materials are molded into a blank to obtain the blank;
[0010] Step 3: Place the shaped blank in a crucible, cover the surface with quartz sand, and place it in a microwave sintering furnace for microwave sintering;
[0011] Step 4: Cool the furnace to room temperature, remove the sintered body, remove the surface sand, and obtain a porous SiO2-SiC ceramic block.
[0012] The quartz sand has a purity of >98% and a particle size of 325 mesh.
[0013] In step one, a three-dimensional mixer is used for dry mixing for 12-24 hours. The speed of the three-dimensional mixer is 20-100 rpm with stepless speed regulation.
[0014] In step two, the mixed raw materials are molded into a blank by placing the mixed powder in a cylindrical pressing mold and holding it under pressure of 10-50 MPa for 40-60 seconds. The blank is obtained by molding, which makes the mixed powder more tightly bound and more likely to generate high-intensity microwave plasma in a microwave field, which can rapidly increase the local temperature and intensify the synthesis reaction.
[0015] In step three, the quartz sand covering the surface has the same particle size as the raw quartz sand, and the thickness of the quartz sand is 0.5-1.5cm. It is sintered in an air atmosphere to prevent oxidation.
[0016] In step three, the microwave sintering temperature is 1100-1350℃, the initial power is 700W, the heating is carried out at a power rate of 100W / min, the holding time is 10-30min, and the microwave heating frequency is 2450MHz.
[0017] Silica has a melting point as high as 1723℃, while microwave sintering temperatures range from 1100-1350℃. Microwave sintering can "melt" silica at temperatures significantly below its melting point by utilizing the unique mechanism of microwave heating and the combination of material morphology and processing. Traditional resistance heating (muffle furnace) conducts heat from the outside in, resulting in uniform temperature, but melting only occurs when the overall thermodynamic melting point (1723℃) is reached. Microwave sintering, however, utilizes the interaction between microwaves and polar molecules (such as dipoles) or ionic defects within the material, generating molecular-level friction and ion conduction losses, directly generating heat from within the material. For materials with strong microwave absorption capabilities, localized or microscopic regions can reach or even exceed the melting temperature at temperatures far below the traditional melting point. During microwave heating, carbon couples, resulting in an internal temperature much higher than the surface temperature. In addition, the reaction of carbon with silicon dioxide produces intermediate products silicon monoxide and carbon monoxide gas, which ionize under microwave action to generate microwave plasma. At 1100-1350℃, it can efficiently absorb microwaves and rapidly heat up to extremely high temperatures (locally exceeding 2000℃). Through heat conduction, it melts the surrounding silicon dioxide. Furthermore, temperature measurement during microwave heating is done using infrared thermometry. The "furnace temperature" measured by microwave sintering is usually a radiation thermometric value, while the local hot spot temperature of the absorber may be hundreds or even thousands of degrees higher.
[0018] The porous SiO2-SiC ceramic preparation method proposed in this invention originates from the observation of phenomena during the microwave synthesis of silicon carbide. Generally, the raw material used in silicon carbide preparation is fine powder, with a particle size typically below 10 μm. After machine pressing, it is microwave sintered, resulting in silicon carbide powder. This invention, however, uses carbon powder with a larger particle size. When the carbon powder particle size is increased and the microwave power is adjusted, the coarse carbon particles rapidly couple with microwave energy, generating localized high temperatures. The carbon reacts with silicon dioxide: SiO2 + C → SiC + CO↑. Simultaneously, unreacted silicon dioxide melts at high temperature, forming a liquid phase that encapsulates the silicon carbide grains and fills the framework. After gas release, pores are naturally formed, and the material solidifies upon cooling to obtain a bulk material. This method integrates the synthesis reaction, pore formation, and sintering densification (through SiO2 liquid-phase bonding) into a single process, requiring no external pore-forming agents, ultimately forming a porous SiO2-SiC ceramic bulk.
[0019] This invention effectively controls the pore size, distribution, and porosity of SiO2-SiC ceramics by adjusting the carbon powder particle size and the silicon-carbon ratio. The invention uses coarse-grained carbon powder with a D50 of 100–300 μm, allowing for rapid localized coupling heating of the carbon particles during microwave heating, forming high-temperature regions. The carbon surface reacts with silicon dioxide at high temperatures, releasing gases, while the silicon dioxide melts, forming a three-dimensional interconnected porous structure. Besides acting as a hotspot to melt the silicon dioxide, carbon also volatilizes, leaving pores. By adjusting the carbon powder particle size and the silicon / carbon ratio, the final pore size and porosity of the ceramic can be effectively controlled. The carbon powder particle size is crucial for the formation of porous ceramics; larger particle sizes result in larger localized high-temperature regions, larger bubbles, and thus larger pores. A higher carbon ratio leads to more gas generation and higher porosity. Heating time affects crystal phase evolution and pore structure stability; excessively long holding times may cause pore collapse. Covering with a thick layer of quartz sand prevents carbon oxidation, maintains a localized reducing atmosphere, and promotes the melting and flow of SiO2.
[0020] This invention overcomes the shortcomings of traditional microwave synthesis of silicon carbide from fine powder, which typically only yields loose powder. By forming a continuous glassy phase through SiO2 melting, the in-situ generated SiC particles are firmly bonded together, directly obtaining a complete porous ceramic block with sufficient strength, eliminating the need for subsequent forming and sintering steps.
[0021] This invention uses common raw materials, eliminating the need for external pore-forming agents and reducing raw material costs. Microwave sintering allows for deep, uniform heating of the material's interior, avoiding localized temperature differences, and spontaneously generating a porous structure, simplifying the process. The process flow requires only three steps: mixing, shaping, and microwave sintering, making it extremely concise. Microwave heating is characterized by its speed, bulk heating, and high energy efficiency. The entire sintering process can be completed within tens of minutes, saving more than 30% energy compared to traditional resistance furnace sintering, making it suitable for large-scale production.
[0022] The beneficial effects of this invention are as follows: The raw materials are simple, requiring no external pore-forming agent; the self-generating gas from the reaction creates pores, avoiding residual contamination from pore-forming agents. The preparation steps are simple, energy consumption is low, and production efficiency is high. By optimizing the microwave sintering process, the coupling efficiency between microwaves and materials can be improved. Adjusting the microwave heating power allows large-sized carbon particles to rapidly couple and generate heat. The high temperature on the carbon surface reacts with silicon dioxide, releasing gas, while the silicon dioxide melts, forming a porous structure. By adjusting the carbon powder particle size and silicon-carbon ratio, the pore size and porosity can be effectively controlled. This invention prepares porous SiO2-SiC ceramics with a three-dimensional interconnected pore structure through a one-step microwave sintering method, showing broad application prospects in fields such as heat insulation, filtration, and catalyst support. Attached Figure Description
[0023] Figure 1 These are macroscopic morphology photographs of the porous SiO2-SiC ceramic bulk material prepared in Example 1 of this invention;
[0024] Figure 2 The XRD pattern of the porous SiO2-SiC ceramic bulk prepared in Example 1 of this invention;
[0025] Figure 3 A scanning electron microscope (SEM) image of the porous SiO2-SiC ceramic prepared in Example 2 of this invention;
[0026] Figure 4 The XRD pattern of the porous SiO2-SiC ceramic bulk material prepared in Example 2 of this invention. Detailed Implementation
[0027] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention.
[0028] It should be noted that, unless otherwise specified, the experimental methods described in the following embodiments are conventional methods; and the reagents and materials used are commercially available unless otherwise specified.
[0029] Example 1:
[0030] At a silicon-to-carbon molar ratio of 1:3, 325-mesh quartz sand and carbon powder with a particle size D50 of 250 μm were mixed in a three-dimensional mixer for 24 hours. The mixed powder was placed in a cylindrical pressing mold and pressed at 20 MPa for 40 seconds to obtain a green body. The formed green body was placed in a corundum crucible, and the surface was covered with 1 cm of quartz sand. It was then placed in a microwave sintering furnace for microwave sintering. The initial power was 700 W, and the temperature was increased to 1350 °C at a power rate of 100 W / min. The temperature was held for 10 min, and the furnace was cooled to room temperature. The sintered body was then removed, and the surface floating sand was cleaned to obtain a porous SiO2-SiC ceramic block.
[0031] Example 2:
[0032] At a silicon-to-carbon molar ratio of 1:3, 325-mesh quartz sand and carbon powder with a particle size D50 of 100 μm were mixed in a three-dimensional mixer for 16 hours. The mixed powder was placed in a cylindrical pressing mold and pressed at 50 MPa for 60 seconds to obtain a green body. The formed green body was placed in an alumina crucible, and the surface was covered with 1.5 cm of quartz sand. It was then placed in a microwave sintering furnace for microwave sintering. The initial power was 700 W, and the temperature was increased to 1200 °C at a power rate of 100 W / min. The holding time was 30 min, and the furnace was cooled to room temperature. The sintered body was removed, and the surface floating sand was removed to obtain a porous SiO2-SiC ceramic block.
[0033] Example 3:
[0034] At a silicon-to-carbon molar ratio of 1:1, 325-mesh quartz sand and carbon powder with a particle size D50 of 250 μm were mixed in a three-dimensional mixer for 24 hours. The mixed powder was then placed in a cylindrical pressing mold and pressed at 10 MPa for 50 seconds to obtain a green body. The formed green body was placed in an alumina crucible, and the surface was covered with 0.5 cm of quartz sand. It was then placed in a microwave sintering furnace for microwave sintering. The initial power was 700 W, and the temperature was increased to 1100 °C at a power rate of 100 W / min. The holding time was 20 min, and the furnace was cooled to room temperature. The sintered body was then removed, and the surface floating sand was removed to obtain a porous SiO2-SiC ceramic block.
[0035] Example 4:
[0036] At a silicon-to-carbon molar ratio of 1:2, 325-mesh quartz sand and carbon powder with a particle size D50 of 250 μm were mixed in a three-dimensional mixer for 12 hours. The mixed powder was then placed in a cylindrical pressing mold and pressed at 10 MPa for 40 seconds to obtain a green body. The formed green body was placed in an alumina crucible, and a 1 cm thick layer of quartz sand was embedded on the surface. It was then placed in a microwave sintering furnace for microwave sintering. The initial power was 700 W, and the temperature was increased to 1200 °C at a power rate of 100 W / min. The temperature was held for 10 minutes, and the furnace was cooled to room temperature. The sintered body was then removed, and the surface floating sand was cleaned to obtain a porous SiO2-SiC ceramic block.
[0037] Comparative example:
[0038] At a silicon-to-carbon molar ratio of 1:2, 325-mesh quartz sand and carbon powder with a particle size D50 of 10 μm were mixed in a three-dimensional mixer for 24 hours. The mixed powder was then placed in a cylindrical pressing mold and pressed at 10 MPa for 40 seconds to obtain a green body. The green body was placed in an alumina crucible, and a 1 cm thick layer of quartz sand was embedded on its surface. It was then placed in a microwave sintering furnace for microwave sintering. The initial power was 700 W, and the temperature was increased to 1200 °C at a power rate of 100 W / min. The temperature was held for 10 min, and the furnace was cooled to room temperature. The sintered body was then removed, and the surface sand was cleaned to obtain silicon carbide powder.
[0039] When conventional fine carbon powder with a particle size D50 of 10μm was used in the comparative example, microwave heating was uniform but there were no local high-temperature zones. The reaction between carbon and silicon dioxide was slow, and the gas release was insufficient to form porous bulk materials.
[0040] The performance of the porous SiO2-SiC ceramic materials prepared in Examples 1-4 was tested, and the test results are shown in the table below.
[0041] Main Indicators of Porous SiO2-SiC Ceramic Materials Prepared in Examples 1-4
[0042]
[0043] As shown in the table above, Examples 1, 3, and 4 all used 250μm carbon powder with relatively large particles, and the silicon-to-carbon molar ratios were 1:3, 1:1, and 1:2, respectively. The higher the carbon proportion in the prepared porous SiO2-SiC ceramic material, the higher its porosity. Figure 1-2 It can be seen that Example 1 uses 250μm carbon powder. Due to the large particle size of the carbon powder, the silica melts with high viscosity, leaving larger pores with a diameter of 50-200μm when the gas evaporates; the heat is more concentrated, the cooling rate is slower, and the silica crystallization is more obvious. Figure 3-4 It can be seen that Example 2 uses 100μm carbon powder, the carbon powder particle size is slightly smaller, and the corresponding pore size is also reduced, with a pore size of less than 20μm; the heat is slightly dispersed, the cooling rate is faster, and the silicon dioxide crystallization is not as obvious as in Example 1.
[0044] This invention proposes a novel method for preparing porous SiO2-SiC ceramics. This method is simple, efficient, energy-saving, and requires no external pore-forming agent. It directly prepares porous SiO2-SiC ceramic blocks with controllable pore structure by generating pores through reaction and using silica melting to form a binder phase. It is suitable for applications such as heat insulation, filtration, and catalyst support.
[0045] The above embodiments are merely examples illustrating the explanation, specific implementation, and effects of the present invention, and are not intended to limit the invention. Based on this disclosure, some modifications or improvements without contributing any inventive step can be made, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of this disclosure fall within the scope of protection claimed in this disclosure.
Claims
1. A method for preparing porous SiO2-SiC ceramics, characterized in that, Includes the following steps: Step 1: Raw material mixing: Mix quartz sand and carbon powder at a silicon-to-carbon molar ratio of 1:1 to 1:
3. The carbon powder particle size D50 is 100-300μm; the quartz sand purity is >98% and the particle size is 325 mesh. Step 2, Compression Molding: The mixed raw materials are molded into a blank to obtain the blank; Step 3: Place the shaped blank in a crucible, cover the surface with quartz sand, and place it in a microwave sintering furnace for microwave sintering; the microwave sintering temperature is 1100-1350℃, the initial power is 700W, the heating is carried out at a power rate of 100W / min, the holding time is 10-30min, and the microwave heating frequency is 2450MHz. Step 4: Cool the furnace to room temperature, remove the sintered body, remove the surface sand, and obtain a porous SiO2-SiC ceramic block.
2. The method for preparing porous SiO2-SiC ceramics according to claim 1, characterized in that: In step one, a three-dimensional mixer is used for dry mixing for 12-24 hours. The speed of the three-dimensional mixer is 20-100 rpm with stepless speed regulation.
3. The method for preparing porous SiO2-SiC ceramics according to claim 1, characterized in that: In step two, the mixed raw materials are molded into tablets by placing the mixed powder in a cylindrical tableting mold and holding it under pressure of 10-50 MPa for 40-60 seconds.
4. The method for preparing porous SiO2-SiC ceramics according to claim 1, characterized in that: In step three, the thickness of the quartz sand covering the surface is 0.5-1.5cm.
Citation Information
Patent Citations
Process for producing silicon carbide through microwave sintering
CN105883812A
Preparation of oriented hole silicon carbide porous ceramic
CN101323524A
Method for preparing silicon carbide porous ceramic by using microwave in-situ sintering technology
CN106565245A